Social movements - Crowley, D.; Marat-Mendes, T.; Falanga, R. (Vocabulary for sustainable consumption and lifestyles: A language for our common future, 2025)
A social movement is a force pushing against something, while also pulling its alternative into being. Diani states that “social movements are defined as networks of informal interactions between a plurality of individuals, groups and/or organizations, engaged in political or cultural conflicts, based on shared collective identities”. For James and Van Seters, a social movement is also characterized by shared objectives: it is a community that “comes together” around a few minimal conditions, as a form of political association between persons who have at least a minimal sense of themselves as connected to others in common purpose and who come together across an extended period of time to effect social change in the name of that purpose.